A Kirkwood-Buff Force Field for polyoxoanions in water - Zou, Jin (Kansas State University, 2010)
The increasing importance of ion-water interactions in the field of chemistry and biology is leading us to examine the structure and dynamic properties of molecules of interest, based on the application of computer-aided models using molecular dynamics simulations. To enable this type of MD study, a molecular mechanics force field was developed and implemented. Kirkwood-Buff theory has been proved to be a powerful tool to provide a link between molecular quantities and corresponding thermodynamic properties. Parameters are the vital basis of a force field. KB integrals and densities were used to guide the development of parameters which could describe the activity of aqueous solutions of interest accurately. In this work, a Kirkwood-Buff Force Field (KBFF) for MD simulation of ammonium sulfate, sodium sulfate, sodium perchlorate and sodium nitrate are presented. Comparison between the KBFF models and existing force fields for ammonium sulfate was also performed and proved that KBFF is very promising. Not only were the experimentally observed KB integrals and density reproduced by KBFF, but other properties like self diffusion constant and relative permittivity are also well produced.
Keywords: Kirkwood-Buff; Polyoxoanions; Force Field; Chemistry, Physical (0494)